2017
DOI: 10.3892/ijo.2017.3916
|View full text |Cite
|
Sign up to set email alerts
|

Effects of irradiation on human leukocyte antigen class I expression in human papillomavirus positive and negative base of tongue and mobile tongue squamous cell carcinoma cell lines

Abstract: Human papillomavirus (HPV) infection is a risk factor for oropharyngeal cancer, besides smoking and alcohol. Patients with HPV-positive tumors have a better prognosis than those with HPV-negative tumors. Furthermore, patients with HPV-positive tumors, with high CD8+ tumor infiltrating lymphocyte counts or absent/low human leukocyte antigen (HLA) class I expression have the best outcome. The latter is paradoxical, since HLA class I expression is important for tumor recognition. Below, the hypothesis that radiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…One report suggests e.g. that IR increases the levels of MHC class I in HPV + OPSCC, thereby allowing for better immune recognition, while another study implies the necessity of an immune system to benefit from IR or chemotherapy (29,30). The role of CD47 has also been investigated, showing that this protein is downregulated upon IR, and that this in turn enhances immune recognition of HPV + OPSCC (31).…”
Section: Discussionmentioning
confidence: 99%
“…One report suggests e.g. that IR increases the levels of MHC class I in HPV + OPSCC, thereby allowing for better immune recognition, while another study implies the necessity of an immune system to benefit from IR or chemotherapy (29,30). The role of CD47 has also been investigated, showing that this protein is downregulated upon IR, and that this in turn enhances immune recognition of HPV + OPSCC (31).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, experimentally, irradiation increased MHC class I expression in vitro in some, but not all, HPV-positive OPSCC cell lines and in one HPV-positive cell line a decrease in HPV16 E5 mRNA expression was also noted (91). Increased MHC class I expression upon irradiation could in part explain why HPV-positive tumors with absent/low MHC class I expression still respond readily to therapy and are recognized by the immune system (91). Eliciting a vigorous immune response in this context, would be in line with data obtained in mice, where HPV-positive tumors were curable after cisplatin or radiation therapy only in immunocompetent and not in immunoincompetent mice (92).…”
Section: Studies Focusing On Immunological and Stem Cell Markers In Tmentioning
confidence: 94%
“…The decrease in MHC class I expression was assumed to be due to active HPV infection and more specifically the downregulation of MHC class I by HPV E5 and E7 (23, 90). MHC class I expression was suggested to increase upon irradiation and make the tumors more sensitive to the immune system of the host (91). Indeed, experimentally, irradiation increased MHC class I expression in vitro in some, but not all, HPV-positive OPSCC cell lines and in one HPV-positive cell line a decrease in HPV16 E5 mRNA expression was also noted (91).…”
Section: Studies Focusing On Immunological and Stem Cell Markers In Tmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unclear, however, whether this really has been studied extensively. Nevertheless, in vitro, it has been experimentally shown that upon irradiation, in some cases, there is an increase in MHC class I expression, while in contrast, HPV16 E5 mRNA is decreased, thereby potentially increasing the immune sensitivity of the tumors [ 102 ]. Achieving increased immune sensitivity of HPV + tumors would be favorable for the clinical outcome and in concordance with experimental data obtained in vivo [ 103 ].…”
Section: The Search Of Prognostic or Targetable Biomarkers In Hpv + And Hpv − Tscc Botscc And Opsccmentioning
confidence: 99%